IMPACT OF REAL-TIME DATA INTEGRATION ON DELAY PREDICTION ACCURACY IN LARGE-SCALE PROJECTS: THE MODERATING EFFECT OF PROJECT COMPLEXITY - Muhammad Nadeem,; Fayyaz Ali,; Ayesha Urooj,; Nawaid Hasan, (Spectrum of Engineering Sciences, 2025)
Purpose: In this paper, the effects of real-time data integration on delay prediction accuracy in large-scale projects are examined, taking into consideration the role of project complexity. Data and Methodology: Based on secondary qualitative analysis of four studies examining the live data systems implementation in projects of different sizes, this research synthesises the findings. Results: The study yields the findings that real-time information enhances the prediction of delay in less complex projects while in the complex ones, the effectiveness is reduced unless enhanced by other analytical tools and data processing techniques. Conclusion: This paper reveals that the advantage of real-time data integration is valid only when the project is considered to be complex. It reveals that to leverage the use of data integration in managing delays in projects, the project management strategies have to be customized to the peculiarities of the particular project. This research contributes to the literature by identifying the contexts in which real-time data integration produces the best results and therefore can help to improve project management in numerous industries.